ANALISIS USAHATANI UNIT BISNIS TANAMAN MUSIMAN DI KEBUN PERCOBAAN FAKULTAS PERTANIAN UNIVERSITAS UDAYANA TAHUN 2017 - Listia Dewi, Ida Ayu; Rantau, I Ketut (JURNAL MANAJEMEN AGRIBISNIS; Vol 6 No 2 (2018): OKTOBER 2018DO - 10.24843/JMA.2018.v06.i02.p07, 2018)
Urban Agriculture is agricultural activity carried out in urban areas. Urban development is running fast. Many shifting agricultural land causes agricultural land in urban areas to become narrow. Denpasar is one example of an urban area that has narrow agricultural land. The choice of the type of product to be cultivated in a narrow area is very important to generate business profits. The purpose of this study was to compare the most profitable seasonal farming activities for urban farming. This research was conducted at the Faculty of Agriculture's Experimental Garden in Unud. Data used such as production, selling price, and production input costs incurred in each of the plant cultivation in the garden during 2017. Respondents used were deliberately determined namely the chairman and treasurer of the plantation manager and also responsible for production and sales. Data analysis used the Gross Margin approach to see which farming activities were the most profitable. The results showed that during the first planting season conducted in February until June 2017 several farming activities were carried out, namely sweet corn farming, Golden melon, Rokcy Melon, Raw Chili, Tomato, and Round Eggplant. The most profitable business is golden melon farming with gross margin value of Rp 797,700 per 100 m2. In the second planting season carried out in July until November 2017 some farming activities were carried out namely Round Eggplant, Raw Chili, Tomato, Glutinous Corn, Sweet Corn, Golden Melon, and Rokcy Melon. The most profitable business in the second planting season is Melon Golden with a Gross Margin value of 881.117 per 100m2.